An initiative to enhance bone health awareness and management for Parkinson's disease patients: a quality improvement project focused on diagnostic testing and fracture risk assessment - Fatima Hamdani; Rogayah Mustafa; Arshiya Khan; Sankkita Vivekananthan; Najah Daud; Sally Bashford (Future Healthcare Journal)
Introduction: Parkinson's disease (PD) is associated with an increased risk of osteoporosis and fractures resulting from factors such as falls caused by postural instability, polypharmacy and muscle weakness. Reduced bone mineral density (BMD), often caused by vitamin D deficiency, disease severity and low BMI, further elevates fracture risk in patients with PD. This quality improvement project (QIP) aimed to improve awareness and bone health testing in patients with PD by focusing on vitamin D, bone profile assessments, DEXA scans, and FRAX scores for fracture risk evaluation and management. Methodology: This QIP involved two cycles focused on managing patients with PD. The first cycle interventions focused on educating doctors through sessions and a poster, whereas the second cycle introduced personalised treatment plans for patients with PD, recorded in their clinical notes. A comparative analysis of post-intervention data was conducted to evaluate the effectiveness of both interventions. Results: Bone profile testing was successfully completed in 100% of patients after both interventions. In cycle 1, 63.3% of patients required vitamin D testing, compared with 25% in cycle 2. Of these, 14.3% received testing after the first intervention, and 100% after the second. However, none of the patients had their FRAX scores calculated or DEXA scans scheduled. The teaching session increased overall confidence among junior doctors in diagnosing osteoporosis from 60% to 70%, and managing osteoporosis from 10% to 80%. It also improved the overall awareness on how to use the FRAX tool from around 50% to 90%. Conclusion: Personalised treatment plans and targeted interventions led to significant improvements in vitamin D testing. However, notable gaps remain in adherence to FRAX calculation and organising DEXA scans. Future efforts should focus on these limitations and ensuring complete bone health assessments for patients with PD. The teaching sessions proved to be highly effective, significantly enhancing participants' understanding of bone health issues in PD.